Analisis Manajemen Media Perum PNRI Lokananta Surakarta di Era Disrupsi Digital - Muadz, Muadz; Riyanto, Buddy (PRoMEDIA, 2023)
Abstract The development of information technology in the music industry has changed the face of the industry as a whole. Digital disruption has forced music industry players to adapt. starting from the process of production, distribution and consumption. The process of consumtion music changes, starting from analog or physical form, to digital form or digital audio streaming platforms. Lokananta, as a state-owned music recording company, has adapted to this challenge. This study examines the media management analysis of Perum PNRI Lokananta in the era of digital disruption. Media management of Lokananta's recorded music in response to the digital disruption era has been implemented,, although the results have not been optimal. The approach used in this research is qualitative with case study method. This study uses two data sources, namely primary data sources and secondary data. Primary data was obtained by conducting interviews with informants and secondary data collection was carried out by reviewing literature.Keywords: Music Recording, Digital Disruption, Media  Management.Abstraksi Perkembangan teknologi informasi dalam industri musik merubah wajah industri secara keseluruhan. Disrupsi digital memaksa pelaku industri musik beradaptasi. mulai dari proses produksi, distribusi dan konsumsi. Proses menikmati musik berubah, mulai dari analog, menikmati dalam bentuk fisik, dalam bentuk digital atau platform digital audio streaming. Lokananta, sebagai perusahaan musik rekaman milik negara beradaptasi menjawab tantangan tersebut. Penelitian ini mengkaji analisis manajemen media Perum PNRI Lokananta dalam era disrupsi digital seperti saat ini. Manajemen media musik rekaman yang dilakukan Perum PNRI Lokananta dalam merespon era disrupsi digital sudah dilakukan, walaupun hasilnya belum maksimal. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif dengan metode studi kasus. Penelitian ini menggunakan dua sumber data, yaitu sumber data primer dan data sekunder. Data primer diperoleh dengan melakukan wawancara kepada narasumber dan pengambilan data sekunder dilakukan dengan mengkaji studi pustaka.Kata Kunci: Musik Rekaman, Disrupsi Digital, Manajemen Media.